2013
DOI: 10.1016/j.dnarep.2012.12.002
|View full text |Cite
|
Sign up to set email alerts
|

RPA provides checkpoint-independent cell cycle arrest and prevents recombination at uncapped telomeres of Saccharomyces cerevisiae

Abstract: Replication Protein A (RPA) is an evolutionary conserved essential complex with single-stranded DNA binding properties that has been implicated in numerous DNA transactions. At damaged telomeres, Saccharomyces cerevisiae RPA recruits the Mec1-Ddc2 module of the DNA damage checkpoint network, its only known function in DNA damage signaling. Here, we describe rfa1 mutants (rfa1-1, rfa1-9, rfa1-10, rfa1-11 and rfa1-12) that are proficient in this checkpoint but nevertheless exhibit deregulation of cell cycle cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…What is the possible protective mechanism induced by inactivation of Rtg pathway? Previously it was shown that the deletions of the DNA-damage checkpoint genes, RAD24 and several other ones, (which are responsible for the arrest) increase the survival of cdc13-1 cells at semi-permissive temperature [ 35 , 36 ]. Therefore we decided to test whether the deletion of RTG3 gene affects the strength of the arrest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…What is the possible protective mechanism induced by inactivation of Rtg pathway? Previously it was shown that the deletions of the DNA-damage checkpoint genes, RAD24 and several other ones, (which are responsible for the arrest) increase the survival of cdc13-1 cells at semi-permissive temperature [ 35 , 36 ]. Therefore we decided to test whether the deletion of RTG3 gene affects the strength of the arrest.…”
Section: Resultsmentioning
confidence: 99%
“…It appeared that, at semi-permissive temperature, the arrest of cdc13-1 single mutant was significantly stronger than the one of cdc13-1 Δrtg3 double mutant (Figure 5B ). Importantly, at non-permissive temperature cdc13-1 Δrad24 cells grow into microcolonies [ 36 ], pointing that a limited number of cell divisions may not be lethal in the absence of functional Cdc13p.…”
Section: Resultsmentioning
confidence: 99%
“…The CST binds single-stranded telomeric repeats through oligosaccharide/oligonucleotide/oligopeptide binding (OB) folds, a common motif in ssDNA and RNA binding proteins (Pennock et al, 2001;Sun et al, 2009Sun et al, , 2011. It has been proposed that the CST outcompetes and replaces RPA at telomeres; however, RPA can also be detected at telomeres and is probably functional during DNA replication (Schramke et al, 2004;Luciano et al, 2012;Grandin & Charbonneau, 2013). Thus, both complexes are able to bind the telomeric repeats, and the division of work between them may be intricately linked to the mechanism of replication at telomeres.…”
Section: The Cst Complexmentioning
confidence: 99%
“…The CST binds single-stranded telomeric repeats through OB folds, a common motif in ssDNA and RNA binding proteins (Figure 1B) 47. It has been proposed that the CST out-competes and replaces RPA at telomeres; however, RPA can also be detected at telomeres, and is probably functional during DNA replication 484950. Thus, a division of work between the CST and RPA must exist, which is probably intricately linked to the mechanism of replication of telomeres.…”
Section: Composition Of Yeast Telomeresmentioning
confidence: 99%